Brand Knowledge Training Through Packaging Materials and the Use of Social Media in Hurung Bunut Village, Gunung Mas District - Susanto, Deri; Natalia, Desi; Jeniva, Isabella; Lianto; Veronica, Maria; Setinawati (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2022)
Hurung Bunut Village is one of the tourist villages in Gunung Mas Regency which was inaugurated in 2016. With the Sapta Pesona label in Hurung Bunut village, the community is invited to participate in regional development. One of the problems faced by the Hurung Bunut village community is brand knowledge. This is evidenced by the lack of special packaging used by the public to market cassava chips, banana chips and Kalulut honey, as well as the lack of social media accounts to promote them. The service task carried out by the Community Service (PkM) team of the Missiology Study Program of the Palangka Raya State Christian Institute focuses on packaging production and the use of social media to promote brands in Hurung Bunut Village. The success of a product brand in the market is supported by its packaging. One of the factors that determine the success of a product brand in the market is supported by packaging aesthetics, packaging design, and promotional materials. In addition, the success of a product in the market depends on how much people know about a product, including through packaging and brand marketing communications on social media. The methodology the Community Service Team uses for the Misiology degree program is the ABCD approach. Through this socialization, Hurung Bunut Village can independently and sustainably promote the brand by applying the knowledge gained from the training provided to achieve the dream of becoming Sapta Pesona.